Kuliatas Pelayanan Ekowisata Mangrove di Ketapang Urban Aquaculture (KUA) Desa Ketapang Mauk Kabupaten Tangerang - Eni Apriliani; Rizkyka Rahma Danti; Amelia Anggraini; Andin Febrianti; Irvan Arif Kurniawan (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study aims to analyze the service quality at Ketapang Urban Aquaculture (KUA), a mangrove ecotourism area in Tangerang Regency, using the Servqual theory encompassing five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. This qualitative research utilized primary data from in-depth interviews with KUA management and secondary data from relevant literature. The findings indicate that physical facilities, such as trekking paths and informative signs, enhance visitor comfort. Educational programs run on schedule, and the complaint system effectively addresses visitor concerns. Friendly and well-trained staff provide a sense of safety and a positive tourism experience. However, challenges remain in optimizing sanitation facilities and digital promotion. The study concludes that KUA's service quality meets expectations, supporting sustainable ecotourism.